Sociological perspectives of social media, rumors, and attacks on minorities: Evidence from Bangladesh - Roy, Sajal; Singh, Ashish Kumar; Kamruzzaman, (Frontiers in Sociology, 2023)
Social media platforms serve as essential modes of communication for billions of people around the world. They host a diverse range of content—from the personal and social to the political serving as an important channel for connecting people for spreading ideas. However, given their widespread penetration into everyday social and political life, they have become a tool for spreading rumors and disinformation that may often misrepresent or distort reality and have in many cases incited violence. In Bangladesh, perpetrators over the last decade have utilized social media platforms to spread rumors and to mobilize mobs to launch violent attacks on minority groups. Drawing from social movement theories on how the nexus between social media and political violence works, this paper examines a sample of five cases during the periods of 2011–2022. We exemplify minority attacks being instigated by social media rumors to understand their nature and causes thereof. The study finds that religious extremism, the absence of legal safeguards, and the culture of impunity are the primary triggers, to a varying degree, for the social media rumor-instigated attacks on minorities in Bangladesh.